Decision Support System Determines the Best Employees at PT Mahkota Group Tbk - Arrahman, Hamzah; Jannah, Miftahul; Akbar , Azi Muhammad (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2023)
This research discusses the development and implementation of a decision support system (DSS) to determine the best employees at PT Mahkota Group Tbk. The main objective of this research is to increase efficiency and objectivity in the decision-making process related to employee performance assessment. The research methodology involves collecting employee performance data, analyzing company needs, and implementing appropriate decision-making models. The SPK developed uses artificial intelligence techniques to process and analyze employee performance data, provide scores, and ultimately determine the best employees based on established criteria. The research results show that the implementation of SPK is able to increase objectivity in assessing employee performance and provide effective support for the decision-making process. With this system, it is hoped that the company can identify and utilize employee potential more optimally, increase productivity, and strengthen the competitiveness of PT Mahkota Group Tbk in the market. This data will be processed and assessed by a system developed using the Simple Additive Weighting (SAW) method. The results of the performance assessment will be presented in the form of ratings and grades for each employee, making it easier for related parties to make a more precise and transparent decision-making process. It is hoped that the results of this research can make a positive contribution to the efficiency and effectiveness of human resource management